Selective cellular imaging with lanthanide‐based upconversion nanoparticles. Issue 4 (2nd January 2019) - Nampi, Padmaja P.; Vakurov, Alexander; Mackenzie, Lewis E.; Scrutton, Nigel S.; Millner, Paul A.; Jose, Gin; Saha, Sikha
Abstract : Upconversion nanoparticles (UCNPs) with sodium yttrium fluoride, NaYF4 (host lattice) doped with Yb 3+ (sensitizer) and Er 3+ (activator) were synthesized via hydrothermal route incorporating polyethyleneimine (PEI) for their long‐term stability in water. The cationic PEI‐modified UCNPs with diameter 20 ± 4 nm showed a zeta potential value of +36.5 mV and showed an intense, visible red luminescence and low‐intensity green emission with 976 nm laser excitation. The particles proven to be nontoxic to endothelial cells, with a 3‐(4, 5‐dimethylthiazol‐2yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay, showing 90% to 100% cell viability, across a wide range of UCNP concentrations (0.3 ng/mL‐0.3 mg/mL) were used in multiphoton imaging. Multiphoton cellular imaging and emission spectroscopy data reported here prove that the UCNPs dispersed in cell culture media are predominantly concentrated in the cytoplasm than the cell nucleus. The energy transfer from PEI‐coated UCNPs to surrounding media for red luminescence in the biological system is also highlighted with spectroscopic measurements. Results of this study propose that UCNPs can, therefore, be used for cytoplasm selective imaging together with multiphoton dyes (eg, 4′, 6‐diamidino‐2‐phenylindole (DAPI)) that are selective to cell nucleus. Abstract : Highly fluorescent water‐dispersible polyethyleneimine‐coated NaYF4 /Yb 3+ /Er 3+ upconversion nanoparticles synthesized using hydrothermal method are promising nontoxic biocompatible materials for imaging cellular cytoplasm.